Association between weight-adjusted waist index and Hashimoto’s thyroiditis: insights from NHANES 2007–2012 - Xiaoyong Wen; Xiaoyong Wen; Yu Mao; Yu Mao; Zeyu Li; Zeyu Li; Guangji Chen; Shiwei Zhou (Frontiers in Nutrition)
ObjectiveWhile previous studies have explored the relationship between obesity and levels of thyroid autoantibodies, research using novel indicators such as weight-adjusted waist index (WWI) remains limited. This study aimed to evaluate the potential relationship between WWI and thyroid autoantibody levels, with the objective of improving our understanding of the links between central obesity and Hashimoto’s thyroiditis (HT).MethodsWe conducted a cross-sectional study using data from the National Health and Nutrition Examination Survey (NHANES) cycles from 2007 to 2012. We analyzed the relationship between WWI and levels of thyroid peroxidase antibodies (TPOAb) and thyroglobulin antibodies (TgAb) through multivariate linear regression and subgroup analyses.ResultsThe study included 7,056 participants with an average age of 49.71 ± 17.66 years, comprising 49.18% females. Mean WWI across the cohort was 11.04 ± 0.84. Analysis revealed a significant positive association between WWI and TPOAb levels (β: 4.78, 95% CI: 1.52, 8.05, p = 0.0041), which remained consistent across all multivariate linear regression models. In contrast, no significant correlation was found between WWI and TgAb levels after adjusting for covariates. Subgroup analysis stratified by gender demonstrated a notable gender-specific effect, where the positive correlation between WWI and TPOAb levels was evident only in females (β: 8.13, 95% CI: 4.14, 12.12, p < 0.0001).ConclusionThis study used WWI as a novel indicator of central obesity and identified a strong association with HT, particularly notable in females. However, further high-quality studies are needed to confirm these findings and explore the underlying biological mechanisms.